Analisis Kebisingan Arus Lalu Lintas terhadap Kegiatan Belajar Mengajar (KBM) di SMA Swasta Surabaya: Susilo Indrawati, Beta Bayu Santika, Suyatno - Susilo Indrawati Susilo Indrawati; Beta Bayu Santika Beta Bayu Santika; Suyatno Suyatno (Jurnal Fisika dan Aplikasinya, 2017)
Noise that we experienced daily are mainly caused by industry, train, plane, and traffic activity. Nowadays, traffic are the min cause for noise, because the noise caused by traffic have systemic cause, meanwhile other source of noise are rather local. Anyone that have activity whether its outside or inside a building near a traffic dense road will be affected by the noise. Noise will affect to the deteriorating of the hearing and child concentration. Khadijah school is one of the school that heavily affected by traffic noise. The school sit near a heavy traffic road, which caused a lot of noise. From the sound pressure level (SPL), the noise caused by the traffic reached 87 dB. The noise criteria (NC) in the parking area of the school reach 78 dB, while inside the school the NC reach 70dB. While according to some research and regulation, the NC in school area should be around 55dB. By analyzing the faade of the classroom wall, its found that the wall have great noise reduction. The faade is made from double wood door with 3cm thickness, 3mm glass windows, and brick wall with 10cm thickness. The material used in the building are up to standard, but it need some adjustment. The first adjustment should be adding an insulation material on the hallway that connected directly to the noise source the second adjustment should be minimalizing the gap in the door and windows by using a rubber so that the noise couldnt pass through the gap.